Rancangan Undang-Undang (RUU) Perampasan Aset: Impian atau Solusi ? - Anggraini, Novellita Sicillia; Indrawati, Ana; Novianto, Andri (Universitas Pahlawan Tuanku Tambusai, 2024)
Eradicating corruption is one of the change programs aimed at building a clean and corruption-free government. The government has made many efforts, starting from establishing the Corruption Eradication Committee (KPK), to eradicating corruption through separate control efforts in the Criminal Code. In this article we will discuss the Asset Confiscation Bill as an opportunity and challenge in eradicating corruption in Indonesia. The drafting method used is the normative legal method, namely paying attention to existing laws and regulations supported by currently valid legal theories. The research results show that the Asset Confiscation Bill has introduced a special mechanism for returning state assets due to corruption without a court decision, thus providing a deterrent effect for the perpetrators. However, it cannot be denied that the implementation of asset confiscation is still hampered by the weak political will of DPR members. Therefore, we can ask the government and legislature to encourage debate and immediately pass the asset confiscation bill.